Upper and lower bounds for the single source capacitated location problem - Cortinhal, M. J.; Captivo, M. E. (European Journal of Operational Research, 2003)
The single source capacitated location problem is considered. Given a set of potential locations and the plant capacities, it must be decided where and how many plants must be open and which clients must be assigned to each open plant. A Lagrangean relaxation is used to obtain lower bounds for this problem. Upper bounds are given by Lagrangean heuristics followed by search methods and by one tabu search metaheuristic. Computational experiments on different sets of problems are presented.